2019
DOI: 10.1007/s10531-019-01811-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and connectivity in fragmented populations of Rhinanthus minor in two regions with contrasting land-use

Abstract: Knowledge of genetic diversity and connectivity within and between populations of specialist meadow plants is crucial to developing effective conservation strategies at the landscape-scale. This study investigated levels of genetic diversity within, and gene flow between populations of a key annual species, Rhinanthus minor in protected meadows and landscape matrix sites in two contrasting regions. Possible barriers to gene flow were also analysed. Leaf material from 714 individuals in an extensively managed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…These discoveries, supported by different statistical methods, highlight the importance of small‐scale genetic studies to determine whether any barriers are restricting gene flow and, ultimately, to prevent further losses of genetic diversity. Identifying population numbers, levels of genetic diversity, and the degree of connectivity between individuals and populations in an anthropized landscape may provide useful information for conservation strategies and demonstrated the importance of preserving the few habitat fragments that remain (Sullivan et al., 2019; Weiss & Leese, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These discoveries, supported by different statistical methods, highlight the importance of small‐scale genetic studies to determine whether any barriers are restricting gene flow and, ultimately, to prevent further losses of genetic diversity. Identifying population numbers, levels of genetic diversity, and the degree of connectivity between individuals and populations in an anthropized landscape may provide useful information for conservation strategies and demonstrated the importance of preserving the few habitat fragments that remain (Sullivan et al., 2019; Weiss & Leese, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The use of microsatellite markers in this study aided in the identifica- demonstrated the importance of preserving the few habitat fragments that remain (Sullivan et al, 2019;Weiss & Leese, 2016).…”
Section: Genetic Diversity Of Myrmecophaga Tridactylamentioning
confidence: 99%
“…A low level of genetic diversity is usually found in small, isolated populations (Jacquemyn et al 2010 ; Crichton et al 2016 ; Sullivan et al 2019 ). The loss of species biodiversity in a given area is one of the main environmental problems (Godefroid et al 2011 ; Brütting 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This also applies to species that currently survive in small quantities as a result of intensified agriculture (Honnay and Jacquemyn 2007 ). Such populations are more susceptible to genetic drift and reduced gene flow between populations (Ellstrand and Elam 1993; Sullivan et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation